KEPEMIMPINAN WANITA: ANALISIS HADIS RIWAYAT ABĪ BAKRAH - Andi Rahman (Ushuluna: Jurnal Ilmu Ushuluddin, 2018)
This study discusses the Hadith of Abī Bakrah, by relating it to the issue of women becoming public leaders. In understanding a hadith, it is necessary to research the hadith from the perspective of matan, asbabul wurud, and analysis of some ulama opinions related to the hadith. Using descriptive analytic methods, this study discusses how leadership in the time of Abī Bakrah and its relevance to the leadership of women that occurred in Indonesia, especially when Megawati became President of Indonesia. This study finds that women's leadership has always been a source of controversy in a variety of views, especially if it seen from the Hadith’s information.